Transnationalism and translation in modern Chinese, English, French and Japanese literatures - Johnson, Ryan (Ryan Stasey) (Anthem Press, 2021)
Drawing on the latest work in comparative philosophy and comparative literature, this book presents an innovative model of transnational literary exchanges.